Regeneration and resurrection in Matthew – Peasants in campo hearing time signals from scribes - Aarde, Andries van (HTS teologiese studies, 2011)
The article aimed to describe the distinctive element in the use of the motif of the resurrection in the Gospel of Matthew in comparison with Mark, Luke and the Sayings Gospel Q. It argued that the distinctive element occurs where parallel texts in Luke 22:24–30, Matthew 19:27–29 and Mark 10:28–31 converge. The distinctive element pertains particularly to the meaning of the Greek expression ‘en tē palingenesia’ in Matthew 19:28. By elaborating on time as a social construct, the article showed how Matthew deals with the conception of time differently than both Mark and Luke. It illustrated that the Gospel of Matthew represents a storyline consisting of a circular movement between ‘genesis’ (Mt 1:1) and ‘palingenesia’ (Mt 19:28), where the word ‘palingenesia’ denotes the meaning ‘regeneration’ rather than ‘resurrection’. Matthew does not narrate an abrupt transition from linear time to clock time. Both co-existed in a world where illiterate peasants and literate scribes scheduled their lives in terms of motifs pertaining to a linear and a punctual conception of time.